Pengaruh Slow Deep Breathing dan Pursed Lip Breathing terhadap Tekanan Darah pada Lansia Penderita Hipertensi - Sabrina Yulian Maharani; Azizah Rahmawati; Fiqi Widyawati; Young Ari Kusworo (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Hypertension in older adults requires continuous management through pharmacological therapy and safe nonpharmacological support. This research aimed to determine the effects of slow deep breathing and pursed lip breathing on blood pressure among older adults with hypertension and to compare the effectiveness of both techniques. This quantitative experimental study used a two group pretest-posttest design. The research was conducted at the Older Adult Integrated Health Post of Ngadiluwih Village, Matesih District, Karanganyar Regency, from May to June 2026. Thirty respondents were selected using purposive sampling and divided into two groups, consisting of 15 respondents in the slow deep breathing group and 15 respondents in the pursed lip breathing group. Systolic and diastolic blood pressure assessments were conducted using a calibrated digital sphygmomanometer, both prior to and following the intervention. The collected data were subjected to statistical examination through the Shapiro-Wilk test, Levene’s test, paired samples t-test, and independent samples t-test. The results showed that both interventions significantly reduced blood pressure. Slow deep breathing produced a greater reduction than pursed lip breathing and may serve as a more effective nonpharmacological adjunct therapy for community-based hypertension management in older adults.